The effect of social support on college students’ sports anomie behavior: the mediating role of self-efficacy and attitude’s regulating role in sports normative behavior - Liu, Liping; Yang, Yuqing; Liu, Han; Chen, Shanping; Shang, Yao; Song, Yifei (Frontiers in Psychology, 2025)
BackgroundCollege students’ sports anomie behavior negatively impacts their physical health, undermines the implementation of the educational philosophies of Fostering Virtue through Education and Health First. There is a lack of quantitative research on the mechanisms underlying such behavior. Based on the Conservation of Resources Theory, this study aims to examine the mechanism through which social support influences college students’ sports anomie behavior.MethodsA total of 2,340 students from 20 universities across China were selected using stratified sampling. Data were collected using the Social Support Scale and the Sports Anomie Behavior Brief Inventory. Mediation and moderation effects were analyzed using AMOS 28.0, SPSS 24.0, and the Process plugin.ResultsSocial support significantly negatively predicted physical misconduct. Physical norm self-efficacy fully mediated the relationship between social support and physical misconduct. Attitudes toward physical norm behavior significantly moderated both the antecedent and subsequent paths of the mediation model.ConclusionThe study validates a moderated mediation model of “social support → physical norm self-efficacy→sports anomie behavior.” Universities should establish a multi-support network involving parents, teachers, and peers, and integrate normative education into physical education curricula. These efforts should synergistically enhance students’ attitudes toward physical norms and self-efficacy from external to internal levels, thereby reducing sports anomie behavior and promoting physical health.